Mechanical properties of boron nitride thin films prepared by atomic layer deposition. Issue 41 (9th October 2017) - Weber, Matthieu; Coy, Emerson; Iatsunskyi, Igor; Yate, Luis; Miele, Philippe; Bechelany, Mikhael
Abstract : Unravelling the relation between heat treatments and resulting mechanical properties of boron nitride thin films prepared by ALD. Abstract : Due to their wide bandgap, boron nitride (BN) thin films are the focus of interest for their potential applications in microelectronic devices. The reliability of these devices is essential and is directly linked to the mechanical properties of the films used for their fabrication. Herein, an atomic layer deposition (ALD) process based on sequential pulses of BBr3 and NH3 at 750 °C is used in order to prepare BN thin films. We report the main physicochemical properties of the films using various analytical methods. We also performed nanoindentation experiments in order to determine the elastic modulus and the hardness. Next, we annealed the films at 1000 and 1350 °C in order to gain understanding on the relation between the annealing temperature, the microstructure obtained and the resulting mechanical properties. Although the hardness of the films presents similar values of 5 ± 1 GPa for all temperatures, it has been found that the elastic modulus increases up to 150 ± 9 GPa when applying an annealing treatment of 1350 °C, which represents a 37% improvement compared to the initial film prepared at 750 °C.